Building An Effective Educational Communication: A Study on Educator-Educatee Relationship in an Effective Teaching and Learning - Sunhaji, Sunhaji (International Conference of Moslem Society, 2018)
This paper discusses about educational communication, particularly in teaching and learning process. Teaching and learning is a dymanic educative interaction process between educators and educatees. Building communication in teaching and learning constitutes an important medium to realize an effective teaching and learning. Effective communication has significant impact on the successful goal achievement. Communication can be said as effective when there is two-way flow of information between communicator and communicant, and this information is equally responded to as expected by both of them. An effective communication is characterized by a good interpersonal relationship. When an effective communication takes place between teachers and educatees during teaching and learning, then it is a successful teaching and learning process. Communication in teaching and learning is highly complex in nature since it involves paedagogical, psychological, and didactical aspects. The paedagogical aspect refers to the fact that teaching and learning take place in an educational environment. Therefore, teachers are demanded to accompany their students to successfully learn and accomplish their competences. The psychological aspect refers to the fact tha students have varied development extents and these require varied materials to be taught, including various varieties in learning, ranging from learning concepts, learning attitudes and learning motoric skills. Finally, the didactic aspect refers to the operational stage of student classroom management in attending the teaching and learning activity. Teaching and learning are said to be effective when the teaching and learning process produces good products, be it the products of instructional effect and nurturant effect. The product of nurturant effect has wider impact as outcome; this nurturant effect is thought as more important as compared to the instructional effect.